Ansiedade materna e relação mãe-bebê - Chemello, Mariana Reichelt (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation deals with maternal anxiety and mother-child relationship, and is composed by two articles, one theoretical and one empirical. In the theoretical article, entitled "Maternal Anxiety and Motherhood: A Systematic Literature Review", a systematic review of the literature was conducted in order to identify and analyze the scientific literature about maternal anxiety and motherhood, published from January 2009 to December 2014. The findings demonstrate the absence of a specific instrument for assessing maternal anxiety and state the importance of identifying anxiety in the prenatal period as a preventive and protective measure for the mental health of mothers, for the baby development and to improve the quality of the relationship of this dyad. In the empirical article, entitled "Maternal anxiety and mother-child relationship: a qualitative study," a qualitative research approach with delineation of Multiple Cases Studies was carried out. The objective was to investigate the phenomenon of maternal anxiety and its manifestation in mothers of babies aged between six and 12 months, trying to identify its impact on the mother-child relationship. In this study participated four mother-child dyads, whose mothers had mild or moderate anxiety. In all these cases it was found that the occurrence of maternal anxiety in the period of pregnancy and early care newborn, reflected somehow in the mother-child relationship. The presented cases corroborate the literature review that shows that anxiety may be related to complications in pregnancy and postpartum, with difficulties in the early care of the newborn, stressors during pregnancy and postpartum, as losses and mourning. Considering the importance that either signs or symptoms of anxiety have during pregnancy, it highlighted the need for further studies with emphasis on the early identification of this phenomenon and the importance of developing and evaluating intervention programs for the control and management of anxiety in the mothers, aiming at prevention and promotion of maternal and child mental health.
Keywords: Ansiedade materna; Maternidade; Relação mãe-bebê; Maternal anxiety; Motherhood; Mother-child relationship; ACCNPQ::Ciências Humanas::Psicologia